2013
DOI: 10.1016/j.jtcvs.2012.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for nonocclusive mesenteric ischemia after elective cardiac surgery

Abstract: A high index of suspicion for NOMI in patients with the above-mentioned risk factors may decrease the diagnostic and therapeutic delay. To identify at-risk patients the developed risk equation is a useful tool with a high specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 25 publications
2
78
1
8
Order By: Relevance
“…It has already been reported that cardiac surgeries increase intestinal permeability leading to gut ischemia resulting in the translocation of microorganisms and endotoxins into the systemic circulation through the portal and lymphatic systems [58], leading to a continuing toxic insult and systemic tissue injury. In addition, surgical trauma itself contributes to the complex inflammatory response that occurs after cardiac procedures [59]. Metformin treatment was given only for two coronary artery disease (CAD) patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been reported that cardiac surgeries increase intestinal permeability leading to gut ischemia resulting in the translocation of microorganisms and endotoxins into the systemic circulation through the portal and lymphatic systems [58], leading to a continuing toxic insult and systemic tissue injury. In addition, surgical trauma itself contributes to the complex inflammatory response that occurs after cardiac procedures [59]. Metformin treatment was given only for two coronary artery disease (CAD) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal circulation leads to a systemic inflammatory response syndrome with hemodynamic changes most commonly involving vasodilation and the need for vasopressor treatment [1,15]. Several studies have documented alterations in gastric microcirculation during extracorporeal circulation [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated the frequent occurrence of nonocclusive mesenteric ischaemia after cardiac and vascular surgery [8][9][10][11] and also in chronic hemodialysis patients [12]. According to these studies, risk factors for the occurrence of a NOMI in cardiovascular patients are increased serum lactate levels > 5 mmmol/L, the application of an intra-aortal balloon pump, and the need for hemodialysis [13]. Additionally, for dialysis patients, the duration of their dialysis and comorbid diabetes mellitus are additional risk factors [12,14].…”
Section: Introductionmentioning
confidence: 99%